Pengukur Kadar Keasaman dan Kekeruhan Air Berbasis Arduino - Saputra, Akip, Ir BAMBANG HARI PURWOTO, M.T, UMIFADLILAH, S.T., M.Eng (2016)
One of the water quality parameters are turbidity and acidity . For the majority of water quality is considered important because it is not just aesthetic .Good water for consumption according to the regulations issued by the government through the Ministry of Health is to have a value of pH 6,5 - 8,5 and maximum turbidity level is 5 NTU ( Nephelometric Turbidity Unit ) ( Permenkes RI number 907 of 2002 , concerning , terms and monitoring of drinking water quality , and the Minister of Health of Indonesia number 416 of 1990 , concerning the conditions and water quality control ) Akan tetapi sebagian besar masyarakat di Indonesia dan khususnya di wilayah karisidenan Surakarta masih ada yang belum mendapat air yang memenuhi kriteria standar baku mutu air. Therefore, the authors plan to make gauges acidity and turbidity of the water to make it easier to identify water to be used.Design tools that authors have the same function with a pH meter or pH meter and water meter or water turbidity meter turbidy who were there and traded in general .This tool uses a series of LED photodiodadan as kekeruhanyang sensor and sensor measures the level of acidity of the liquid kekeruhanair as a pH sensor. Processing the results of measurements performed by sensors using arduino uno , whereas to display the measurement results using the LCD . This tool has a limit of detection of water turbidity between 0-20 NTU ( Nephelometric Turbidity Unit ) and the degree of acidity ( pH ) of 0 - 14. This measure relatively accurately by using the power supply baterai9v are widely available in the market so that it can be taken everywhere - where to facilitate the use of current research or field surveys .With nearly 100 % accuracy percentage of the average value of measuring acidity of 98 % and the average value of measuring turbidity 99 % while the value of the average error range of each sensor is 0.5 in the measuring acidity or 2 % and 0.2 on turbidity measurement or 1 % by means of comparison , it can be concluded that the tool is good for use as a detector acidity and turbidity. Keywords: Acidity, arduino measuring pH, turbidity